Morphology in a Parallel, Distributed, Interactive Architecture of Language Production - Kapatsinski, Vsevolod (Frontiers in Artificial Intelligence, 2022)
How do speakers produce novel words? This programmatic paper synthesizes research in linguistics and neuroscience to argue for a parallel distributed architecture of the language system, in which distributed semantic representations activate competing form chunks in parallel. This process accounts for both the synchronic phenomenon of paradigm uniformity and the diachronic process of paradigm leveling; i.e., the shaping or reshaping of relatively infrequent forms by semantically-related forms of higher frequency. However, it also raises the question of how leveling is avoided. A negative feedback cycle is argued to be responsible. The negative feedback cycle suppresses activated form chunks with unintended semantics or connotations and allows the speaker to decide when to begin speaking. The negative feedback cycle explains away much of the evidence for paradigmatic mappings, allowing more of the grammar to be described with only direct form-meaning mappings / constructions. However, there remains an important residue of cases for which paradigmatic mappings are necessary. I show that these cases can be accounted for by spreading activation down paradigmatic associations as the source of the activation is being inhibited by negative feedback. The negative feedback cycle provides a mechanistic explanation for several phenomena in language change that have so far eluded usage-based accounts. In particular, it provides a mechanism for degrammaticalization and affix liberation (e.g., the detachment of -holic from the context(s) in which it occurs), explaining how chunks can gain productivity despite occurring in a single fixed context. It also provides a novel perspective on paradigm gaps. Directions for future work are outlined.